Evaluation of some Biochemical and Hematological Parameters in Patients with Chronic Kidney Disease - AlAni, Hadeel T.; Al-Lami, Makarim Q. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Chronic kidney disease is a condition that results from an indefinite change in the structure and function of the kidneys. A slow, steady progression characterizes it and is irreversible. Objectives: This study aims to evaluate the findings of certain biochemical and hematological tests in samples from Iraqi CKD patients. Methods: This study included 90 subjects, where 70 patients with chronic kidney disease and 20 healthy individuals. Blood samples were collected from the patients during their visits to Ghazi Al-Hariri Surgical Specialties' Hospital- Medical City, Baghdad, Iraq. Age, sex and body mass index were assessed for each participant followed by renal function tests [serum blood urea, creatinine, uric acid and estimated glomerular filtration rate], and complete blood count. Also, serum levels of uromodulin and cystatin C were measured statistically studies were carried out using analysis of variance (ANOVA).Results:  the study demonstrated a highly significant (P